When Back of Pack Meets Front of Pack: How Salient and Simplified Nutrition Labels Affect Food Sales in Supermarkets. (April 2018) - Elshiewy, Ossama; Boztug, Yasemin
Back-of-package (BOP) nutrition information appears ineffective against increasing obesity rates. Therefore, federal agencies increasingly promote front-of-package (FOP) nutrition labels. Despite the public attention the topic has received in recent years, research is still short of evidence about the effectiveness of FOP nutrition labels in real-life settings. To add to extant literature, this study uses individual-level purchase data to analyze the impact of adding simplified FOP nutrition labels when BOP information is already available. Consumers reduced the number of calories contained in their purchases for products that started carrying a simplified FOP nutrition label. Furthermore, results show a long-term (short-term) decrease in price (promotion) sensitivity for these products after label introduction. These findings suggest that simplified FOP nutrition labels can induce healthier purchases in supermarkets compared with when only BOP nutrition information is available.